Suppression of bacterial wilt in susceptible scion of tomato (Solanum lycopersicum) and brinjal (Solanum melongena) using Solanum torvum as resistant rootstock - Yenare, Snehal; Daspute, Abhijit Arun; Raut, Vijay; Babar, Nikita; Wagh`, Sopan Ganpatrao; Sonar, Shreyas; Thole, Shreyans; Vitekar, Vallabh; Harke, Sanjay (Current Horticulture, 2023)
The autografts of tomato (Lycopersicon esculentum L.), brinjal (Solanum melongena L.) chilli (Capsicum sp.), and citrus (Citrus spp.), showed 86, 87, 84, and 88 % graft efficiency respectively. Moreover, homograft of tomato, brinjal and citrus showed 83, 81 and 84% graft efficiency respectively. In vitro microgafting protocol performed within 8 days after seed germination and had up to 97% success rate without use of any phytohormones. Moreover, tomato and brinlal grafted on S. torvum rootstock showed the resistance to bacterial wilt. However, non -grafted tomato and brinjal showed bacterial wilt symptoms. The developed microgarted protocol helps in the production of bacterial wilt resistant tomato and brinjal by the use of S. torvum as a rootstock.